A systematic review of the effects of lavender oil on primary dysmenorrhea - Ji-Ah, Song; Woo, Oh, Jae (Edelweiss Applied Science and Technology, 2025)
The purpose of this systematic review was to investigate lavender oil interventions for women experiencing primary dysmenorrhea and to determine the effectiveness of these interventions on dysmenorrhea. Six national and international databases were reviewed to retrieve and collect literature published up to August 8, 2024, describing randomized controlled trials of lavender oil interventions for women’s dysmenorrhea. Two researchers independently screened the literature through abstracts and full-text articles. As a result of the literature search, a total of 174 articles were searched, and 158 of them were reviewed, excluding 16 duplicate articles. Of these, 31 articles were reviewed, excluding 127 articles not related to PICO, resulting in a final selection of 7 articles. A meta-analysis showed that lavender oil produces a 1.56-point reduction in women’s dysmenorrhea when compared to a placebo group. Aromatherapy with lavender oil alone has been shown to be effective in reducing dysmenorrhea.